2020
DOI: 10.1186/s13075-020-02352-3
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate functions are altered in the osteoarthritic cartilage

Abstract: Background Heparan sulfate (HS) proteoglycans (PG) may be found at the chondrocyte surface and in the pericellular cartilage matrix, and are involved in cell-cell and cell-matrix interactions. An important function of HS chains is to regulate cell fate through specific interactions with heparin-binding proteins (HBP) modulated by their complex sulfation pattern. Osteoarthritis (OA) is a joint disorder characterized by the degradation of articular cartilaginous extracellular matrix. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Additionally, total CAGs, CS, and heparan sulfate/heparin (HS/H) were reported to be higher in plasma of RA patients than in plasma of healthy subjects 27 . Moreover, the sulfation of HS was reported to be increased in cartilages of patients with OA 28 , and a decreased HS content or a reduced sulfation level was reported to protect against OA progression by regulating protease activity 25 . Thus, the significant depletion of HS degradation in microbial function would prevent HS from being degraded, promoting arthritis progression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, total CAGs, CS, and heparan sulfate/heparin (HS/H) were reported to be higher in plasma of RA patients than in plasma of healthy subjects 27 . Moreover, the sulfation of HS was reported to be increased in cartilages of patients with OA 28 , and a decreased HS content or a reduced sulfation level was reported to protect against OA progression by regulating protease activity 25 . Thus, the significant depletion of HS degradation in microbial function would prevent HS from being degraded, promoting arthritis progression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…24 We found that the significant depletion of DS degradation would inhibit the production of chondroitin 4-sulfate ( figure 3B ), which might hurt the mechanical properties of the articular cartilage. 24 Moreover, the significant depletion of HS degradation might be a potential cause of the higher plasma level of HS observed in RA and OA patients, 25,26 which could promote arthritis progression by regulating protease activity. 27 The most driving species of DS degradation and HS degradation were MGS Bacteroides uniformis and MGS Bacteroides plebeius , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulphation patterns of GAGs are critical to the binding of serpin exosites [ 81 ]. In cartilage, sulphation has been shown to be important for GAG binding of ADAMTS-5 and TIMP-3 [ 78 ], and the sulphation pattern of important cartilage GAGs changes in OA, which may impact on their function in the tissue [ 82 , 83 ].…”
Section: Common Modes Of Serpin Regulation and Their Implications For Joint Tissuesmentioning
confidence: 99%
“…Osteoarthritis (OA), one of the age-related debilitating and degenerative diseases, is often clinically characterized by joint pain, limited movement, and transient morning stiffness ( Shamdani et al, 2020 ). Mechanistically, cartilage degradation, synovial inflammation, and subchondral bone remodeling are involved in the pathological development of OA ( Dai et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%